“A past that opens up the future”. An approach from the anthropology of memory to Retroperspectivas, de Diego Reynaga (Clepsidra - Interdisciplinary Journal of Memory Studies, 2024)
Part of an incipient investigation, in this article we propose to approach the book Retroperspectivas. The reconstruction of memory from the perspective of a son of a disappeared woman, of Diego Andrés Reynaga, son of Ana María Sosa, a militant detained-disappeared in 1976 in the province of Tucumán, Argentina. Positioned in the field of memory studies, first of all, we briefly situate the state of the question of “children's literature”, as the Argentine narratives of children of the seventies generation of militancy are known, where we register this production from the interior of the country. Secondly and without deviating from the field, we propose to think about this “experiential essay” in the light of concepts coming from the anthropology of memory –“territory of memory” (Da Silva Catela, 2001), “transmission” and memory as “art” of narration” (Candau, 2006)–, from which we analyze scenes where significant aspects of the construction of collective memory, its forgetfulness and its silences are plotted. Finally, we conclude about the potential of literary writing in memory processes.
Keywords: Children's Literature, Memory Territory, Transmission, Tucumán